Морфологічні особливості плодів Crambe koktebelica та Crambe mitridatis (Brassicaceae) - Каліста, М.С.; Щербакова, О.Ф.; Попович, А.В. (Український ботанічний журнал, 2014)
Проведен сравнительный анализ морфологических
особенностей плодов C. koktebelica и C. mitridatis из locus
classicus и других известных местонахождений в пределах их
ареала. Уточнены и дополнены диагностирующие признаки
морфологии плода, которые можно использовать для
определения этих видов. Уточнен ареал обоих видов. Comparative analysis of morphological peculiarities of fruits of
C. koktebelica and C. mitridatis from locus classicus and another
well-known locations in their natural habitats was performed. The
diagnostic features of the fruit morphology, which could be used
to identify these species, were made more precise and amplified.
The natural ranges for both species were specified.